Pembuatan Display Penunjuk Arah dan Nama Objek Wisata di Kawasan Agro Edu Wisata - Nurwathi Nurwathi; Erna Garnia; Rangga Satria Perdana; Muhamad Fahrulrozi; Lisya Maharani (TECHNO-SOCIO EKONOMIKA, 2025)
The development of Agro-Educational Tourism is now growing rapidly as an effort to restore the community's economy through the tourism and agriculture sectors. Sindulang Village, Sumedang Regency, is located in the Gunung Kereceng area and is one of the potential locations for developing Agro-Educational Tourism. The challenges faced in managing this area include the need for integrated tourism management and educational capabilities to enhance the visitor experience. Additionally, some visitors get lost due to the lack of directional signs. Therefore, it is necessary to create more displays to reduce difficulties in reaching the intended location. This study aims to design and create directional signboards and tourist attraction name boards in the Baruimun-Hill, applying the principles of ergonomics. The research steps included problem analysis, site surveys, data collection from 44 students, data calculation, followed the creation and installation of the display. Ergonomic principles were applied in determining the dimensions of the letters, the distance, and the color to ensure readability and visual appeal. As a result, the directional signs have a visibility distance of 18 meters with a letter height of 90 mm, while the tourist attraction signs have a visibility distance of 50 meters with a letter height of 250 mm. The combination of a brown background and white lettering was chosen for its high contrast and suitability to the environment. This implementation not only makes it easier for visitors but also enhances the tourist experience, supports the development of the tourist area, and creates visual with ergonomic principles.